ISOLASI DAN IDENTIFIKASI BAKTERI ENDOFIT DARI TANAMAN PADI (Oryza sativa) SEBAGAI PENGENDALI PENYAKIT HAWAR DAUN BAKTERI AKIBAT Xanthomonas oryzae pv. oryzae - Serdani, Army Dita; Aini, Luqman Qurata; Abadi, Abdul Latief (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2018)
Rice cultivation often face obstacles, and one of them is bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv. oryzae (Xoo). The application of endophytic bacteria is one of solutions to overcome this problem. Endophytic bacteria are non-pathogenic bacteria, which live in plant tissues. These bacteria could be isolated from the plant tissues. They may adapt to the plant tissues and produce antibiosis that could increase the plant resistance. Therefore, objectives of the research were to isolate the endophytic bacteria from healthy plant tissues and to identify them through morphology, physiology, biochemistry, and molecular. Method of the research was explorative along with three principal activities, such as isolation, selection, and identification on the potential endophytic bacteria. The isolation of the endophytic bacteria from healthy rice tissues has resulted 53 isolates and five of them have antagonistic ability in vitro against Xoo. Isolate ak9 has the highest antagonistic ability, 7.67 mm, in comparison with other isolates. Results of identification showed that those five potential bacteria have close relations, such as da3 with Bacillus cereus, isolate ak9 with Burkholderia sp., isolate ak30 with Enterobacter sp and isolate da9, as well as ak15 are Corynebacterium sp.